AMERICA FIRST: ASSESSING THE ECONOMIC IMPACT OF THE FIRST TRUMP ADMINISTRATION - Liviu RADU; Carmen RADU (Challenges of the Knowledge Society, 2025)
The Trump administration (2017-2021) implemented a series of significant economic reforms, having a profound impact on the United States economy. Among the most notable measures were tax reductions through the Tax Cuts and Jobs Act (2017), protectionist policies and the trade war with China, economic deregulation, and stimulus measures during the COVID-19 crisis. This paper analyzes the effects of these policies on key economic indicators such as GDP, employment, and inflation, comparing the economic performance of the Trump administration with that of previous administrations. The study uses statistical data to highlight the short- and long-term impact of the adopted economic measures.